Immunogenicity of DNA Vaccines Encoding Simian Immunodeficiency Virus Antigen Targeted to Dendritic Cells in Rhesus Macaques - Tenbusch, Matthias (Public Library of Science, 2012)
BACKGROUND: Targeting antigens encoded by DNA vaccines to dendritic cells (DCs) in the presence of adjuvants enhances their immunogenicity and efficacy in mice. METHODOLOGY/PRINCIPAL FINDINGS: To explore the immunogenicity of this approach in non-human primates, we generated a single chain antibody to the antigen uptake receptor DEC-205 expressed on rhesus macaque DCs. DNA vaccines encoding this single chain antibody fused to the SIV capsid protein were delivered to six monkeys each by either intramuscular electroporation or conventional intramuscular injection co-injected or not with poly ICLC, a stabilized poly I: C analogue, as adjuvant. Antibodies to capsid were induced by the DC-targeting and non-targeting control DNA delivered by electroporation while conventional DNA immunization at a 10-fold higher dose of DNA failed to induce detectable humoral immune responses. Substantial cellular immune responses were also observed after DNA electroporation of both DNAs, but stronger responses were induced by the non-targeting vaccine. Conventional immunization with the DC-targeting DNA at a 10-fold higher dose did not give rise to substantial cellular immune responses, neither when co-injected with poly ICLC. CONCLUSIONS/SIGNIFICANCE: The study confirms the potent immunogenicity of DNA vaccines delivered by electroporation. Targeting the DNA via a single chain antibody to DEC-205 expressed by DCs, however, does not improve the immunogenicity of the antigens in non-human primates.